Effects of demand-feeding and dietary protein level on nitrogen metabolism and symbiont dinitrogen gas production of common carp (Cyprinus carpio, L.) - Mes, Wouter; Kersten, Philippe; Maas, Roel M.; Eding, Ep H.; Jetten, Mike S. M.; Siepel, Henk; Lücker, Sebastian; Gorissen, Marnix; Van Kessel, Maartje A. H. J. (Frontiers in Physiology, 2023)
Ammonia accumulation is a major challenge in intensive aquaculture, where fish are fed protein-rich diets in large rations, resulting in increased ammonia production when amino acids are metabolized as energy source. Ammonia is primarily excreted via the gills, which have been found to harbor nitrogen-cycle bacteria that convert ammonia into dinitrogen gas (N2¬) and therefore present a potential in situ detoxifying mechanism. Here, we determined the impact of feeding strategies (demand-feeding and batch-feeding) with two dietary protein levels on growth, nitrogen excretion, and nitrogen metabolism in common carp (Cyprinus carpio, L.) in a 3-week feeding experiment. Demand-fed fish exhibited significantly higher growth rates, though with lower feed efficiency. When corrected for feed intake, nitrogen excretion was not impacted by feeding strategy or dietary protein, but demand-fed fish had significantly more nitrogen unaccounted for in the nitrogen balance and less retained nitrogen. N2 production of individual fish was measured in all experimental groups, and production rates were in the same order of magnitude as the amount of nitrogen unaccounted for, thus potentially explaining the missing nitrogen in the balance. N2 production by carp was also observed when groups of fish were kept in metabolic chambers. Demand feeding furthermore caused a significant increase in hepatic glutamate dehydrogenase activities, indicating elevated ammonia production. However, branchial ammonia transporter expression levels in these animals were stable or decreased. Together, our results suggest that feeding strategy impacts fish growth and nitrogen metabolism, and that conversion of ammonia to N2 by nitrogen cycle bacteria in the gills may explain the unaccounted nitrogen in the balance.